Lessons for a SECURE Future: Evaluating Diversity in Crop Biotechnology Across Regulatory Regimes - George, Dalton R.; Hornstein, Eli D.; Clower, Carrie A.; Coomber, Allison L.; Dillard, DeShae; Mugwanya, Nassib; Pezzini, Daniela T.; Rozowski, Casey (Frontiers in Bioengineering and Biotechnology, 2022)
Regulation of next-generation crops in the United States under the newly implemented “SECURE” rule promises to diversify innovation in agricultural biotechnology. Specifically, SECURE promises to expand the number of products eligible for regulatory exemption, which proponents theorize will increase the variety of traits, genes, organisms, and developers involved in developing crop biotechnology. However, few data-driven studies have looked back at the history of crop biotechnology to understand how specific regulatory pathways have affected diversity in crop biotechnology and how those patterns might change over time. In this article, we draw upon 30 years of regulatory submission data to 1) understand historical diversification trends across the landscape and history of past crop biotechnology regulatory pathways and 2) forecast how the new SECURE regulations might affect future diversification trends. Our goal is to apply an empirical approach to exploring the relationship between regulation and diversity in crop biotechnology and provide a basis for future data-driven analysis of regulatory outcomes. Based on our analysis, we suggest that diversity in crop biotechnology does not follow a single trajectory dictated by shifts in regulation, and outcomes of SECURE might be more varied and restrictive despite the revamped exemption categories. In addition, the concept of confidential business information and its relationship to past and future biotechnology regulation is reviewed in light of our analysis.